Comparison between the Claudin-3 and the Ratio of Monocyte to High-Density Lipoprotein Cholesterol as Markers for Psoriasis in a Sample of Iraqi Patients - Ghassan A. Al-Shamma, Yasser N. Ahmed, Abdullah Salih Hassen (Pakistan Journal of Medical & Health Sciences, 2022)
The index score of psoriasis severity (PASI) cannot always be of value as a marker in non- plaque psoriasis. Alternative biomarkers have been used for the diagnosis and prognosis of the disease. Among these markers are the transmembrane protein Claudin-3 and the Monocyte to High- density lipoprotein cholesterol Ratio (MHR). Objective: The present work was carried on to evaluate the prognostic and diagnostic ability of the two biomarkers for psoriasis, Claudin-3 and MHR, relate them to the PASI score in psoriatic patients, and find the correlation between the two markers. Subjects and methods: forty patients with psoriasis (25 males and 15 females) of 7.3 ±3.7 years disease duration, and 30 healthy control subjects of 19 males and 11 females were enrolled in the study from March to July 2021. The following tests were done for each patient and control subjects: Complete blood count (CBC) by VCS Technology Hemoglobinometry, Claudin-3 by ELISA technique, and serum lipids by enzymatic spectrophotometric methods. Results: Both markers (Claudin-3 and MHR) showed significantly higher values in the patient’s group than their controls in a manner proportional to the severity of the disease. As diagnostic markers, the receiver operating characteristic curve (ROC) analysis for both of them gave acceptable sensitivity and specificity. Conclusion: Claudin-3 and MHR can be used alternatively as adjuvant diagnostic and prognostic markers to PASI score for psoriasis.